Pengaruh Experiential Marketing, Service Quality, Brand Image, Price, dan Customer Expectations Terhadap Customer Satisfaction pada Bioskop XXI Gresik - Rohdlotul Aisy Rofidah; Wenti Krisnawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the influence of experiential marketing, service quality, brand image, price, and customer expectations on customer satisfaction at XXI Cinema Gresik. The research method used is a quantitative approach by distributing questionnaires to 240 respondents. The results show that the variables of experiential marketing, service quality, price, and customer expectations have a significant influence on customer satisfaction while the brand image variable does not have a significant effect on customer satisfaction. In conclusion, companies are advised to improve service quality and experience-based marketing strategies.